Effect Of Ladder Training On Skill Performance Among Soccer Players (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of the study was to examine the effect of ladder training on skill performance among soccer players. In this study, forty (40) soccer players (age 13 to 14) from NEROCA Football Club, Imphal East, Manipur were selected randomly and assigned into two groups as experimental group (N=20) and control group (N=20). The selected skill performance as Dribbling (Figure 8 Dribbling Test) and Foot Juggling (Instep Juggling Test) were employed as tool for the study. The test is implemented as pre and post-test for both groups to find out the effectiveness of ladder training on skill performance. The experimental group has undergone one hour training program, five times a week for six weeks. The 0.05 levels of significance were fixed to find out the difference between the group means by employing the descriptive and pair t-test statistical techniques.  The ladder training for the experimental group made significant difference in the selected skill performance test but in case of control group no significant difference was found.